(untitled) (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
HIDDEN MEANING OF EMBLEMS AND ARCHITECTURAL SCULPTURES ON CRACOW TOWNHOUSES One of the oldest identification signs on Cracow’s townhouses were emblems. They were usually sculptures in stone, stuccoes, and, more rarely, paintings. The oldest date from the 14th century. Despite changing times, styles and testes, this tradition survived as long as up to the 20th century. The reasons for placing emblems on houses were varied. Most often their purpose was to advertise an inn, a pharmacy, a shop or a craftsman’s workshop. In other events, they referred to the owner of the house. In such cases it was the patron saint, who was supposed to protect the house. In the 19th century new symbols appeared, but despite their symbolic and alluding character, they did not win the name of „house emblems”. There may be different reasons for this. When they appeared on the houses which had older names, naturally the tradition prevailed. Symbols were widely used in emblems, and in many cases today their meaning is not clear to us. The example of this can be the Pod Jaszczurką House (the Lizard House). It dates from the end of the 15th century. The name was distorted in the 20th century, and now it is popular under the faulty name „Jaszczury” (the Lizards), which clearly shows that meaning of this name was not understood. Assuming that the emblem can be explained as a symbol of a salamander, which used to be called „jaszczurka” (the lizard) in older times, the author tries to explain three meanings of the symbol of a salamander, two Christian, and one pagan and magic. In addition, the article discusses two other sculptures on the façades of Cracow townhouses, one from the turn of the 18th/19th century, and the latter from the first half of the 19th century. These sculptures cannot literally be called emblems of the houses, but the symbols and allusion in them has not be explained so far. This article is the first attempt at such an explanation.